Recent reconstruction of deep-water macrofaunal communities recorded in Continental Margin sediments in the Balearic Basin. (July 2017) - Cartes, J.E.; Schirone, A.; Barsanti, M.; Delbono, I.; Martínez-Aliaga, A.; Lombarte, A.
Abstract: We present an initial reconstruction of recent (last few centuries) mud-bottom faunal communities on the upper slope (398–667 m) of the continental margin off Catalonia (western Mediterranean), including periods free of any trawling impact. Radiometric dating of marine sediments and identification of faunal remains (e.g., fish otoliths, pteropod shells, coral sclerites) were performed to obtain a sediment geochronology in a 56 cm sediment core (MC4) taken at 398 m off the Ebro Delta in 2011. Core MC4 was especially rich in faunal remains, including, for example, 247 identifiable otoliths. A fine-scale chronology of MC4 was not possible due to sediment mixing. However, the depth of 210 Pbxs penetration (20–22 cm) identified sediments older (below 22 cm depth) and younger (from core top to 22 cm) than ca. 100 years. Mass Accumulation Rate (MAR) from the 210 Pbxs profile was estimated as 0.23±0.02 g cm −2 y −1 . A significant peak of sclerites of the bamboo coral Isidella elongata was found between 4 and 8 cm in MC4, with remains of the axes and bases of Isidella colonies exclusively found at core depths >8–10 cm, which would correspond (MAR results) to the period 1980–1985. Such structures were not found in the 0–8 cm layer, likely an effect of trawling that started in the area in the 1980s. Other changes both in benthos (corals and cirripedes) and zooplankton (pteropods) seemed to be related with Ebro river discharge, with changes coinciding with massive damming of the Ebro and tributary rivers in the 1950s and until 1965. Mesopelagic fish also showed temporal oscillations in MC4. Abundance of some myctophid remains ( Lampanyctus croccodilus and Benthosema glaciale ) was related with positive NAO periods and with rather high temperature in Levantine Intermediate Waters. By contrast, periods of higher dominance of Ceratoscopelus maderensis off Catalonian coasts could indicate lower salinity during the past and a progressive degree of eutrophication in intermediate waters in recent decades. A general decline in myctophids otolith abundance during the last ca. 100 years could be related to changes in the temperature and salinity of deep-water masses and a decline in ocean productivity that would also have affected open-water fish stocks. Highlights: We did a first reconstruction of recent deep-sea assemblages based on faunal remains in sediment cores. A peak of corals ( Isidella elongata ) sclerites was related with the starting of trawling. Other changes (in benthos and pteropods) seemed to be related with Ebro river damming. Mesopelagic fish composition showed temporal oscillations in sediment cores. Changes in mytophids abundance were related with NAO and changes in water masses.